Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1128/jcm.41.11.4924-4929.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rectoanal Mucosal Swab Culture Is More Sensitive Than Fecal Culture and Distinguishes Escherichia coli O157:H7-Colonized Cattle and Those Transiently Shedding the Same Organism

Abstract: Enrichment and direct (nonenrichment) rectoanal mucosal swab (RAMS) culture techniques were developed and compared to traditional fecal culture for the detection of Escherichia coli O157:H7 in experimentally infected and naturally infected cattle. Holstein steers (n ‫؍‬ 16) orally dosed with E. coli O157:H7 were sampled after bacterial colonization starting 15 days postinoculation. Enrichment RAMS cultures (70.31% positive) were more sensitive than enrichment fecal cultures with 10 g of feces (46.88% positive)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 42 publications
11
114
2
1
Order By: Relevance
“…The number of E. coli O157: H7/g feces ranged from 3.5 ϫ 10 5 CFU/g to levels detectable only by enrichment culture (defined as Ͻ10 1 CFU/g). The pattern of carriage of E. coli O157:H7 by the experimentally inoculated steers was similar to that of cattle carrying the bacteria naturally, showing wide variation in duration of fecal positive status and in fecal counts of E. coli O157:H7 (1,11,14,18,24,26).…”
Section: Resultsmentioning
confidence: 71%
“…The number of E. coli O157: H7/g feces ranged from 3.5 ϫ 10 5 CFU/g to levels detectable only by enrichment culture (defined as Ͻ10 1 CFU/g). The pattern of carriage of E. coli O157:H7 by the experimentally inoculated steers was similar to that of cattle carrying the bacteria naturally, showing wide variation in duration of fecal positive status and in fecal counts of E. coli O157:H7 (1,11,14,18,24,26).…”
Section: Resultsmentioning
confidence: 71%
“…Recently, the recto-anal junction (RAJ) mucosa was identified as the primary site of E. coli O157:H7 colonization in cattle (47). Based on this finding, we demonstrated that culture of recto-anal mucosal swabs (RAMS) is easier and more sensitive than fecal culture to detect the bacteria (51) and that administration of E. coli O157:H7 to the terminal rectal mucosa is a reliable method to establish colonized cattle experimentally (58). Development of effective interventions to reduce bovine carriage of E. coli O157:H7 will rely on understanding the bacterial factors involved in E. coli O157:H7 colonization and persistence at the RAJ mucosa.…”
mentioning
confidence: 94%
“…To isolate and identify E. coli O157 strains from bovine samples, D-sorbitol MacConkey agar plates supplemented with 4-methylumbelliferyl-␤-D-glucuronide (MUG), cefixime, and potassium tellurite (SMAC-CTM) (40) or D-sorbitol agar plates supplemented with neutral red and MUG (SNM) (17 g of Bacto Peptone, 3 g of yeast extract, 5 g of NaCl, 10 g of D-sorbitol, 0.3% neutral red, 15 g of Bacto Agar, 0.1 g of MUG [pH 7.3] per liter of distilled water) were used. Trypticase soy broth (TSB; BBL/Becton Dickinson) was used for enrichment culture as previously described (40). For the motility assay, 0.3% soft agar (10 g of tryptone, 3 g of NaCl, 3 g of agar per liter of distilled water) was used.…”
Section: Methodsmentioning
confidence: 99%